2018
DOI: 10.1186/s12931-018-0830-z
|View full text |Cite
|
Sign up to set email alerts
|

Indacaterol/glycopyrronium versus salmeterol/fluticasone in the prevention of clinically important deterioration in COPD: results from the FLAME study

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a progressive disease and a composite endpoint could be an indicator of treatment effect on disease worsening. This post-hoc analysis assessed whether indacaterol/glycopyrronium (IND/GLY) 110/50 μg once daily reduced the risk of clinically important deterioration (CID) versus salmeterol/fluticasone (SFC) 50/500 μg twice daily in moderate-to-very severe COPD patients from the FLAME study.MethodsCID was defined as ≥100 mL decrease in forced expiratory vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…At the time of writing, there is limited evidence on the risk of a composite CID in studies comparing LAMA/LABA and ICS/ LABA. A post hoc analysis of data from the FLAME study showed a 28% reduction in the risk of a first short-term deterioration with LAMA/LABA compared with ICS/LABA (hazard ratio: 0.72; 95% CI: 0.67, 0.78; P < 0.001) [53]. The composite CID endpoint includes the occurrence of a moderate/severe exacerbation, and so the reduction in CID risk should be interpreted with caution due to the mixed evidence regarding the relative effects of LAMA/LABA and LABA/ICS on exacerbation risk.…”
Section: Short-term Deterioration Of Copdmentioning
confidence: 99%
“…At the time of writing, there is limited evidence on the risk of a composite CID in studies comparing LAMA/LABA and ICS/ LABA. A post hoc analysis of data from the FLAME study showed a 28% reduction in the risk of a first short-term deterioration with LAMA/LABA compared with ICS/LABA (hazard ratio: 0.72; 95% CI: 0.67, 0.78; P < 0.001) [53]. The composite CID endpoint includes the occurrence of a moderate/severe exacerbation, and so the reduction in CID risk should be interpreted with caution due to the mixed evidence regarding the relative effects of LAMA/LABA and LABA/ICS on exacerbation risk.…”
Section: Short-term Deterioration Of Copdmentioning
confidence: 99%
“…Local spirometric norms were used [31]. COPD exacerbation was defined as an acute event characterized by a deterioration of the patient's respiratory symptoms that are beyond the normal day-to-day variations and which leads to treatment modification [32].…”
Section: Introductionmentioning
confidence: 99%
“…In our study we found that the individual CID components contributed substantially to the total CID rate, with the effects of BUD/FORM versus FORM on CID generally reflected by the individual components. A post-hoc analysis of the FLAME study [16], in which the effect of indacaterol/glycopyrronium versus salmeterol/ fluticasone on CID was evaluated in patients with an exacerbation history, showed a greater effect of the dual bronchodilator on CID prevention. The largest effect was seen on FEV 1 deteriorations, consistent with other bronchodilator studies [1,[3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%